Determinan Pengungkapan Corporate Social Responsibility Pada Industri Manufaktur - Dwi Astutik; Daniel Adi Setya Rahardjo; Ivan Permana; Asri Winanti Madyoningrum; Zahra Dinul Khaq (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the influence of corporate governance determinants, particularly the presence of an independent board of commissioners and an audit committee, on the level of Corporate Social Responsibility (CSR) disclosure. The study focuses on manufacturing sector companies listed on the Indonesia Stock Exchange. Using a quantitative approach, the study population included 228 companies, and through purposive sampling technique, 92 companies met the criteria during a three-year observation period, resulting in a total of 276 observational data. Data analysis was conducted using multiple linear regression with a least squares approach, preceded by classical assumption testing to ensure model validity. The results show that the presence of an independent board of commissioners and an audit committee significantly influences CSR disclosure. This finding indicates that both elements can serve as instruments for implementing Good Corporate Governance (GCG) principles, encouraging companies to be more transparent and responsible in communicating their social activities to stakeholders. The implications of these results emphasize the importance of strengthening governance structures in encouraging more optimal CSR practices, as well as contributing to academic literature and managerial practice in the fields of accounting and sustainability management.